2005
DOI: 10.1086/428109
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Evolution of the Sun in Time: High‐Resolution X‐Ray Spectroscopy of Solar Analogs with Different Ages

Abstract: We investigate the long-term evolution of X-ray coronae of solar analogs based on high-resolution X-ray spectroscopy and photometry with XMM-Newton. Six nearby main-sequence G stars with ages between ≈ 0.1 Gyr and ≈ 1.6 Gyr and rotation periods between ≈ 1 d and 12.4 d have been observed. We use the X-ray spectra to derive coronal element abundances of C, N, O, Ne, Mg, Si, S, and Fe and the coronal emission measure distribution (EMD). We find that the abundances change from an inverse-First Ionization Potentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
250
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(282 citation statements)
references
References 77 publications
32
250
0
Order By: Relevance
“…The coronal abundances of the same two stars were derived by Sanz-Forcada et al (2004) and by Telleschi et al (2005) 4 respectively, with an analysis of XMM-Newton data similar to ours. We then computed the coronal/photospheric abundance ratios of all the solar-type dwarfs in our sample, excluding HD 283572 because of its peculiar evolutionary phase and extreme activity level.…”
Section: τ Boo: a Medium-activity Coronal Sourcesupporting
confidence: 72%
See 1 more Smart Citation
“…The coronal abundances of the same two stars were derived by Sanz-Forcada et al (2004) and by Telleschi et al (2005) 4 respectively, with an analysis of XMM-Newton data similar to ours. We then computed the coronal/photospheric abundance ratios of all the solar-type dwarfs in our sample, excluding HD 283572 because of its peculiar evolutionary phase and extreme activity level.…”
Section: τ Boo: a Medium-activity Coronal Sourcesupporting
confidence: 72%
“…7 shows a comparison of its EMD distribution vs. temperature (Method 1) with those of other four G-K stars: the Sun (G2V, Peres et al 2000), κ 1 Ceti (G5V, Telleschi et al 2005), Eri (K2V, Sanz-Forcada et al 2004), andHD 283572 (G2IV, Scelsi et al 2005).…”
Section: τ Boo: a Medium-activity Coronal Sourcementioning
confidence: 99%
“…Studies have used X-rays and extreme ultraviolet radiation to find α mostly in the range of 2-2.5 for G-M dwarfs (Audard et al 2000;Kashyap et al 2002;Güdel et al 2003) and for T Tauri stars (Stelzer et al 2007), supporting the view that moderate flares are the dominant heating source for these active coronae. This observation may indeed be the basis for the correlation between radio and soft X-ray emission in magnetically active stars and flares, the high level of apparently constant emission being the result of a large number of comparatively small flares not individually detected in the light curves (Telleschi et al 2005).…”
mentioning
confidence: 74%
“…The relations are well represented by power laws, as illustrated in Figure 4. From band-integrated luminosities and individual lines (see Telleschi et al 2005 for X-ray lines) the following decay laws are found for chromospheric, transition region UV, transition region FUV, EUV (including the softest X-rays at 20-100Å), and soft X-rays (1-20Å), where we also use the rotation law in Eq. (2.2): …”
Section: The Radiative History Of Magnetically Active Starsmentioning
confidence: 99%
“…Finally, the active regions and flares in the upper chromosphere, transition regions and coronae as well as solar-like winds have been studied thanks to the UV, and EUV data from, e.g., IUE, HST, GALEX, EUVE and FUSE (e.g., Jordan et al 1987;Ayres 1995, Pagano et al 2004, Ribas et al 2005, Wood et al 2005, X-ray data from, e.g., Einstein, Rosat, ASCA, Beppo-SAX, Chandra, and XMM (e.g., Favata & Micela 2003 and reference therein, Telleschi et al 2005, Stelzer 2007), and radio observations from VLA, VLBI, VLBA, and single-dishes (e.g., Güdel & Benz 1993, Benz & Güdel 1994, Umana et al 1995, Trigilio et al 1998.…”
Section: Sources Of Long-term Data On Magnetic Activitymentioning
confidence: 99%